2015
DOI: 10.1002/anie.201507473
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Imaging In Vivo at Wavelengths beyond 1500 nm

Abstract: Compared to imaging in the visible and near-infrared regions below 900 nm, imaging in the second near-infrared window (NIR-II, 1000-1700 nm) is a promising method for deep-tissue high-resolution optical imaging in vivo mainly owing to the reduced scattering of photons traversing through biological tissues. Herein, semiconducting single-walled carbon nanotubes with large diameters were used for in vivo fluorescence imaging in the long-wavelength NIR region (1500-1700 nm, NIR-IIb). With this imaging agent, 3-4 μ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
257
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 335 publications
(258 citation statements)
references
References 26 publications
0
257
0
1
Order By: Relevance
“…The tradeoff between increased resolution and decreased imaging speed at longer imaging wavelength stresses the need for fluorescent emitters with high QYs and tunable emission linewidths that maximize the ratio of emitted photons per given spectral region. Our new generation of CSS QDs achieves a 2–3 order of magnitude increase in QY compared with commonly employed SWIR-emissive CNTs212 across the entire sensitivity range of modern SWIR cameras while exhibiting narrow emission linewidths. As a result, CSS QDs not only facilitate multiplexed fluorescence imaging, but also enhance imaging speed for high-resolution imaging at long imaging wavelengths through improved particle quality and the resulting enhancement in QY.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The tradeoff between increased resolution and decreased imaging speed at longer imaging wavelength stresses the need for fluorescent emitters with high QYs and tunable emission linewidths that maximize the ratio of emitted photons per given spectral region. Our new generation of CSS QDs achieves a 2–3 order of magnitude increase in QY compared with commonly employed SWIR-emissive CNTs212 across the entire sensitivity range of modern SWIR cameras while exhibiting narrow emission linewidths. As a result, CSS QDs not only facilitate multiplexed fluorescence imaging, but also enhance imaging speed for high-resolution imaging at long imaging wavelengths through improved particle quality and the resulting enhancement in QY.…”
Section: Resultsmentioning
confidence: 97%
“…With QYs of 16% at the red edge of the sensitivity range of SWIR cameras, our probes are more than six times brighter than previously published InAs-based QD systems and further maintain high QYs in aqueous media after phase transfer. Ultimately, we demonstrate how our SWIR fluorophores exhibit a 2–3 order of magnitude higher QY than CNTs212 across the entire sensitivity range of SWIR cameras and demonstrate their use in non-invasive through-skull fluorescence imaging in mice. The improved material properties position our InAs CSS QDs as the material of choice for SWIR fluorescence imaging and suggest possible use in other applications such as SWIR LEDs, photovoltaics, photodetectors and photon upconversion devices15161718.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…[10a–e, 11] We recently reported that epifluorescence imaging in the NIR-IIa window (1,300–1,400 nm) and NIR-IIb window (1,500–1,700nm) afforded an imaging depth of 2–3 mm (compared to ~ 0.2 mm imaging depth in NIR-I) in the brain of mice capable of sub-10 microns and sub-5 microns cerebrovascular imaging resolutions, respectively. [12] This was further aided with the capability of video rate dynamic imaging to follow vascular hemodynamics. [12] Thus far, carbon nanotubes and inorganic nanoparticles are the most commonly used NIR-II fluorescent agents for in vivo imaging with the caveat of slow excretion of nanomaterials from the body and side effects concerns.…”
mentioning
confidence: 99%
“…Especially, over-1000-nm (OTN-) NIR fluorescence imaging has attracted much attention because NIR light in this region can penetrate the body more deeply than the commonly used first biological window (NIR-I: 700-900 nm) region [5][6][7][8][9][10]. The OTN-NIR region is also called the second (NIR-II or NIR-IIa: 1000-1350 nm) and third (NIR-III or NIR-IIb: 1550-1850 nm) biological windows [11].…”
Section: Introductionmentioning
confidence: 99%